2011
DOI: 10.3390/cancers3010494
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Management of Pancreatic Cancer

Abstract: Pancreatic cancer is one of the most deadly solid tumors, with an overall 5-year survival rate of less than 5%. Due to a non-specific clinical presentation, it is often diagnosed at an advanced stage and is rarely amenable for curative treatment. Therefore early diagnosis and appropriate staging are still essential to define the best care and to improve patient survival. Several imaging modalities are currently available for the evaluation of pancreatic cancer. This review focuses on different techniques and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…This phenomenon was observed in other studies on abdominal ultrasonography. Dabizzi et al, 9 showed that the sensitivity of ultrasonography in detecting pancreatic tumors can reach 95%, which is consistent with the results of our study. In addition, Michl et al 10 demonstrated that ultrasonography may have similar sensitivity to that of CT for detecting small lesions (<2 cm, cT1), especially when advanced imaging techniques are used.…”
Section: Discussion Diagnostic Accuracy For Establishing T Categoriessupporting
confidence: 93%
See 1 more Smart Citation
“…This phenomenon was observed in other studies on abdominal ultrasonography. Dabizzi et al, 9 showed that the sensitivity of ultrasonography in detecting pancreatic tumors can reach 95%, which is consistent with the results of our study. In addition, Michl et al 10 demonstrated that ultrasonography may have similar sensitivity to that of CT for detecting small lesions (<2 cm, cT1), especially when advanced imaging techniques are used.…”
Section: Discussion Diagnostic Accuracy For Establishing T Categoriessupporting
confidence: 93%
“…33 Other studies reported a higher accuracy of abdominal ultrasonography, reaching 80% to 96% when the color Doppler mode was used. 7,9,31 Minniti et al 21 reported the accuracy of ultrasonography to be 81.4%, which was lower than that of CT (86%). The advancement in surgical techniques has enabled to use resection for more advanced pancreatic tumors.…”
Section: Discussion Diagnostic Accuracy For Establishing T Categoriesmentioning
confidence: 98%
“…The sensitivity of US is ~ 95% if the lesion is more than 3 cm. With CT, which is the method of choice for evaluating patients with symptoms that are suggestive of the disease, lesions larger than 1.5 cm are detected at 100% but smaller lesions have a sensitivity of 77% and a specificity of 100% (27). The high soft tissue contrast of MRI provides an attractive option in staging PDAC (27).…”
Section: Discussionmentioning
confidence: 99%
“…With CT, which is the method of choice for evaluating patients with symptoms that are suggestive of the disease, lesions larger than 1.5 cm are detected at 100% but smaller lesions have a sensitivity of 77% and a specificity of 100% (27). The high soft tissue contrast of MRI provides an attractive option in staging PDAC (27). The desmoplastic stroma of PDAC prevents the delivery of contrast agents resulting in an absence of hyperintensity in the tumor compared to normal parenchyma that is useful in guiding resection and staging (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation